O papel da polícia judiciária junto à Justiça Restaurativa: a mediação policial no NECRIM como meio alternativo na resolução de conflitos - Gandolfi, Renan Luís de Azevedo (2023)
The central objective of this work is to analyze and study the role played by the Judiciary Police with Restorative Justice in the face of restorative molds of state interference in the face of criminal conduct, if it occurs. In this context, the main issues involving the paradigm of the conventional criminal system are addressed, pointing out and reflecting the legitimacy and efficiency of the current punitive system, considering the new role played by the judicial police in social control, in addition to the importance of the victim in the sphere of criminal justice. criminal. Collaborative methods of mediation and conciliation will be analyzed, comparing which is most appropriate for restorative justice purposes, with a special focus on police mediation. The central hypothesis developed in this research revolves around the feasibility of implementing restorative justice in the police sphere and the legal and extra-legal effects resulting from this approach. To support this analysis, data from police mediation centers linked to the Civil Police of São Paulo and elsewhere are presented, as a basis for questioning the new project of the criminal procedure code and also to demonstrate, through empirical evidence, the effectiveness of the procedure adopted by the Special Criminal Nuclei (NECRIM's). It is concluded that the adoption of restorative justice in the area of the judicial police plays an essential role in transforming the current paradigm of response to crime by the Brazilian criminal system. Such an approach promotes a closer relationship between the police forces and society, contributes to the humanization of police agents, reduces the number of cases referred to the Special Criminal Courts, reduces criminal recidivism and prevents the occurrence of more serious crimes. The study was conducted based on a review of the available literature, and data collection was performed electronically